Factors that Affect Students with Learning Disabilities Inability to Master Writing Skills - Nazatul Raha binti Abdul Raof; Mohd Mokhtar Tahar (International Inclusion Development and Cooperation, 2023)
Writing abilities are intimately tied to sophisticated cognitive abilities, and they provide challenges for both instructors and students during teaching and learning sessions in terms of their jobs and roles. This study's goal is to evaluate a few factors that contribute to students with special educational needs at PPKI's lack of writing proficiency. This concept paper is the result of a library investigation including the gathering of knowledge and academic resources about the role that learning disabilities have been shown to have in student achievement as well as recommendations to help students with special educational needs become more proficient writers. The findings of the library research also indicate that several disability-related characteristics ex occupational therapy approaches. The outcomes of the library research also demonstrate the existence of several disability-related characteristics, including legibility, speed, pausing while writing, and pressure applied to the pencil during writing. Occupational therapy approaches, multisensory techniques, support and collaboration between teachers and parents increase the mastery of writing skills among MBPK are recommended by this study.